A novel idea to increase the performance of a wheat flour cyclone separator: Controlling the reverse flow - Aghaei, Ehsan; Rostampour, Vahid; Rezvanivand Fanaei, Adel; Nikbakht, Ali M.; Jolius, Gimbun (Wiley, 2023)
In this study, as a novelty, the reverse flow effect on a wheat flour cyclone performance was evaluated. A computational fluid dynamics (CFD) simulation was realized using a Reynolds stress turbulence model. Also, particle–air interactions were modeled applying a discrete phase model. Besides the experimental measurement, the numerical simulation was conducted in a main (without reverse flow) and six various reverse flow levels (I = 0.0385 m3 s−1, II = 0.0396 m3 s−1, III = 0.0484 m3 s−1, IV = 0.0583 m3 s−1, V = 0.0704 m3 s−1, and VI = 0.0836 m3 s−1) by CFD. The validation between pressure drop in experimental data and numerical results revealed a good agreement with a maximum deviation of 8.2%. Cyclone performance including pressure drop and separation efficiency was assessed in the mentioned reverse flow levels. Moreover, velocity field, centrifugal force, and turbulence parameter were evaluated, comprehensively. It was found that the flour separation efficiency increased with enhancing the reverse flow level to IV = 0.0583 m3 s−1, but decreased with a sharp slope in the reverse levels of V = 0.0704 m3 s−1 and VI = 0.0836 m3 s−1.